Breastfeeding Benefits: A Comprehensive Review of Maternal and Infant Health Outcomes - Gandodi, Vedavathi Sai; Krishna, Ambati Vamsi; Padarthi, Pavankumar; Sandeep, Doppalapudi; Chakravarthy, Adusumalli (Indian Journal of Pharmacy Practice)
The current review examines numerous breastfeeding’s consequences on health of baby and mother. Breastfeeding is an important step to be taken by every mother which could be a boon for the baby in providing proper growth and immunity, especially for the first six months. It also helps in creating a strong bond between parent and child. Infants’ entire health, including their immune systems is benefited by breast milk’s immunological properties, microbes and nutritional components. The review also discussed the factors that affect how long and exclusively a woman breastfeeds, classifying these factors into social, biological, biological, psychological and hospital-related variables. The importance of supportive language and healthcare interventions is emphasized. Furthermore, the review delves into the psychological, cognitive and brain development impacts of breastfeeding on children. It underlines the possible links between autism spectrum condition and nursing, as well as the positive cognitive, neurological and social-emotional results associated with breastfeeding. The effects of nursing on maternal affect, mood and postpartum depression were also explored in this review. It concludes by underscoring the need for a comprehensive approach to promoting successful breastfeeding, considering the diverse factors that influence both infant and maternal health.
Keywords: Breastfeeding; Benefit; Milk; Challenges; Remedies